Influence of Cutting Size and Plant Growth Regulators on the Vegetative Propagation of Jatropha curcas Linn. - Ashraf, M.; Gill, R.I.S.; Singh, Baljit (Indian Journal of Agroforestry, 2020)
Jatropha curcas has evoked much interest globally as a potential bio-diesel plant and for its role in sustainable development of the wastelands. A wide range of yield and oil content have been reported in different seed sources. There is a need to standardize vegetative propagation technique for large scale true to type multiplication of elite germplasm. In this direction, studies were carried out to standardize the cutting size and pre-planting auxin treatments. Amongst the five cutting sizes, the 40 cm cutting length produced the highest values of various plant growth parameters. Amongst the six pre-planting treatments of growth regulators, maximum sprouting (89.23%), collar diameter (3.59 cm) and total root length (4.83 m) were recorded in cuttings pre-treated with 100 ppm IBA for 24 hours.